DAYA TARIK PENUMPANG TERHADAP TRANSPORTASI KERETA CEPAT WHOOSH - Nurwijayanti, Utari (Study of Applied Entrepreneurship, 2024)
This study aims to measure and analyze the level of public attraction to the Whoosh Experience Program, as well as its impact on increasing awareness and interest in the presence of the Jakarta-Bandung High Speed Train service. Based on data on the number of tickets sold, it can be seen that the level of public attraction is always increasing. The survey results also show high public interest in the presence of this fast train. A smart marketing strategy is the key to KCIC's success in increasing public appeal to choose to use their services. A well-planned strategy, a way of communicating the product to the public that is considered attractive and the price policy decision set is well received among the public, especially users of public transportation services. This success is the basis for the Whoosh fast train to become one of the results of the development of technological projects from the public transportation sector in Indonesia and create an attraction that can be enjoyed by the entire community.